Engineering closed-cell structure in lightweight and flexible carbon foam composite for high-efficient electromagnetic interference shielding. (September 2018) - Sun, Yimin; Luo, Shaohong; Sun, Helei; Zeng, Wei; Ling, Chenxi; Chen, Dugang; Chan, Vincent; Liao, Kin
Abstract: In this work, we develop a specifically engineered variant of carbonized melamine foam (cMF) by carrying systematic structural modifications with Au nanoparticles, graphene (G), Fe3 O4 (IO) and poly(dimethyl siloxane) (PDMS). Our main goal is to construct a lightweight and flexible cMF composite with tailored 3D hierarchical architecture for achieving high-efficiency in electromagnetic interference (EMI) shielding. By capitalizing on the synergistic effect of the multifunctional components in the fabrication of the typical closed-cell structure, cMF-Au-G-IO/PDMS composite produced herein demonstrates superior physical properties including low density (116 mg/cm 3 ), high conductivity (81.3 S/m), large specific surface area (708 m 2 /g), proven superparamagnetism (Ms = 22.6 emu/g), and moderate compressive strength (110 KPa), collectively leading to the significant attenuation effect towards EMI. The cumulative EMI shielding effectiveness (SE) of cMF-Au-G-IO/PDMS film with a thickness of 2 mm is determined as 30.5 dB in X band (8.2–12.4 GHz). Interestingly, SE is further raised up to 52.5 dB when the film thickness is increased to 10 mm. Hence, we envision the emergence of multifunctional cMF-based composite as a promising engineering system for fulfilling the demanding applications in EMI shielding. Graphical abstract: Image 1